The impact of the 2024 coral bleaching event on corals at a remote atoll in the Tuamotu Archipelago, French Polynesia - Matthieu Juncker; Xavier Raick; Carla Chevillard; David Varillon; Christophe Menkes; Swen Jullien; Bastien Pagli; Maxime Duphil; Sandrine Job; Laetitia Hédouin; David Lecchini (Coral Reefs, 2026)
Coral reefs are under severe threat from global warming, particularly due to the increasing frequency of mass coral bleaching events. This study documents the effects of the fourth global coral bleaching event on corals of Tahanea, a remote uninhabited French Polynesian atoll over a 10-month period. Coral surveys (transects and tracking of individual colonies) and temperature monitoring were conducted by one in situ observer. The marine heatwave lasted 80 days, from January 24, 2024, to April 12, 2024, with a peak intensity of + 1.55 °C above climatological levels. This event was the longest in the past 30 years in the South Pacific region as well as the most intense in terms of cumulative intensity (79.2 °C·days) and daily degree heating week (DHW) annual maximum (reaching 4.7 °C weeks −1 ). In May 2024, 11–16% of coral colonies showed signs of bleaching, while 27–43% were recently dead. By September, out of the 40 studied large colonies, 50% of corals partially bleached in April were dead, and 80% of those fully bleached in April had died. In September 2024, underwater visual surveys (depth: 0.4–2 m) revealed low live coral cover (15%), with old dead coral dominating substrate composition at Tahanea. This study shows that even isolated, uninhabited coral reefs, far from any direct human pressure, are highly vulnerable to marine heatwaves. This highlights the importance of rapid and drastic reductions in greenhouse gas emissions to conserve coral reefs.

Suspended particulate matter in Voh lagoon (New Caledonia): Impact of ultramafic rock mining on primary production - Sandrine Chifflet; Jean-Louis Gonzalez; David Varillon; Anne Desnues; Bernard Angeletti; Adrien Duvivier; Doriane Delanghe; Cristèle Chevalier (Regional Studies in Marine Science, 2026)

Three‐dimensional conservation planning of fish biodiversity metrics to achieve the deep‐sea 30×30 conservation target - Laetitia Mathon; Florian Baletaud; Anne Lebourges‐Dhaussy; Gaël Lecellier; Christophe Menkes; Céline Bachelier; Claire Bonneville; Tony Dejean; Mahé Dumas; Sylvie Fiat; Jacques Grelet; Jérémie Habasque; et al. (Conservation Biology, 2025)
Accelerating rate of human impact and environmental change severely affects marine biodiversity and increases the urgency to implement the Convention on Biological Diversity (CBD) 30×30 plan for conserving 30% of sea areas by 2030. However, area‐based conservation targets are complex to identify in a 3‐dimensional (3D) ocean where deep‐sea features such as seamounts have been seldom studied mostly due to challenging methodologies to implement at great depths. Yet, the use of emerging technologies, such as environmental DNA combined with modern modeling frameworks, could help address the problem. We collected environmental DNA, echosounder acoustic, and video data at 15 seamounts and deep island slopes across the Coral Sea. We modeled 7 fish community metrics and the abundances of 45 individual species and molecular operational taxonomic units (MOTUs) in benthic and pelagic waters (down to 600‐m deep) with boosted regression trees and generalized joint attribute models to describe biodiversity on seamounts and deep slopes and identify 3D protection solutions for achieving the CBD area target in New Caledonia (1.4 million km 2 ). We prioritized the identified conservation units in a 3D space, based on various biodiversity targets, to meet the goal of protecting at least 30% of the spatial domain, with a focus on areas with high biodiversity. The relationship between biodiversity protection targets and the spatial area protected by the solution was linear. The scenario protecting 30% of each biodiversity metric preserved almost 30% of the considered spatial domain and accounted for the 3D distribution of biodiversity. Our study paves the way for the use of combined data collection methodologies to improve biodiversity estimates in 3D structured marine environments for the selection of conservation areas and for the use of biodiversity targets to achieve area‐based international targets.

Zooplankton in Kone Lagoon (New Caledonia): Natural variability versus mining effects - Marc Pagano; Martine Rodier; Marine Laval; David Varillon; Loïc Guilloux; Cécile Dupouy; Jean-Luc Devenon; Cristèle Chevalier (Marine Pollution Bulletin, 2025)

Variability of the Sea Surface Salinity (SSS) in the Western Tropical Pacific: On the Ability of an OGCM to Simulate the SSS, and on the Sampling of an Operating Merchant Ship SSS Network - Mansour Ioualalen; Yoshinobu Wakata; Yoshikazu Kawahara; Yves Gouriou; David Varillon (Journal of Oceanography, 2003)